Geomorphological mapping of the San Lorenzo area Sant'arcangelo region Southern Italy - Muh Aris Marfai (Indonesian Journal of Geography, 2005)
The study area is located in the Sant'arcangelo region, Southern Italy. The area was developed from late Pliocene to middle Pleistocene in the southern part of the Apenines chain. It has also been defined as a piggy back basin filled with siliciclastic deposits, controlled by sedimentary tectonic activity.This article aims to identify the geological condition and generating geomorphological map for San Lorenzo area using aerial photo (scale 1:15000) and Panchromatic SPOT image (Scale 1:66000). Image interpretation was also done to identify morphological, structural and processes.The Sant'Arcangelo region is composed of 4 cycles both marine and continental in origin, all deposited on different environments: The Caliandro, Agri, San Lorenzo and Sauro cycles. The study area consists of Sauro and San Lorenzo Cycle. Sauro Cycle is Comprises of three heterotrophic units deposited in sintectonic discordance over the Agri cycle. San Lorenzo Cycle lying in unconformity over the precedent cycles is consisting of three units, namely conglomerates on the base part as well as on the top part of the sequence, and silty clays in the intermediate part. They form a syncline structure which ax has a NW-SE direction. The main structural features are represented by the San Lorenzo syncline and the Alianello fault. The San Lorenzo area has three principal origins: alluvial, denudation, and structural. Due to the geological-tectonic complexity, the structural landform is normally found as structural denudational landform. San Lorenzo area comprises of 41 landform units, namely 3 units of alluvial landforni, 26 units of denudational landform and 11 units of structural denudational landform.